The State of Nursing and Future Issues in Isolated Island - Todoroki, Kumiko; Kitagishi, Megumi; Hasegawa, Kouichi; Fuyuki, Hiroko; Tokie, Daijiro; Kurata, Takayo; Sugiyama, Mutsumi (Journal of Health Care in Islands, 2012)
We introduced the present condition of the nursing business in the Oshima health center, andproposed the future subject. Characteristics are as follows;（1）In addition to routine work, as aspecial feature, clinical inspections and recuperation-at-home support, etc. are added, and we serveas a part of work of an inspecting engineer or MSW.（2）We deal with wide condition from ofpatient's correspondence emergency, chronic disease to end period.（3）Our chronic dialysis hastied up with Nephrologist as part of a telemedicine model, leading to reduction of urgent dialysis atnight. According to the questionnaire to nurses, good human relations, wide spectrum of duties andthe polite nursing care were raised as a strong point. And the following points surfaced as for thefuture subject, maintenance of the manual, a share of experience between staffs and putting furtheringenuity.